A weighted plus/minus metric for individual soccer player performance - Schultze, S. R.; Wellbrock, C.-M. (Journal of Sports Analytics, 2018)
Despite soccer being the number one sport in the world in many respects, the "beautiful game" still lags behind other sports in terms of analytics. We propose a weighted plus/minus metric to be used as an instrument to evaluate player performance. An unweighted plus/minus metric subtracts goals conceded from goals scored for each player while on the field of play and are regularly used in hockey or basketball. Key improvements to this established, unweighted +/- metric include control for opponents` strength, the importance of a particular goal, and considerations for the fact that scoring is less frequent in soccer. The results from three teams (Bayern Munich, VfL Wolfsburg, Werder Bremen) in the German Bundesliga from the 2012-13 season were used as a demonstration and comparison of the two metrics. In addition to the creation of a weighted +/- system, a spatial mapping system of team shots was developed to give a potential visual explanation of why certain players were a net positive/negative influence for their team.